Influence of Fertilizer and Mulch Types on Growth and Yield of Curly Chili (Capsicum annuum L.) - Jeane Claudea Tanjung; Bayu Dwi Apri Nugroho; Hanggar Ganara Mawandha; Aristya Ardhitama; Indah Retno Wulan (Jurnal Teknik Pertanian Lampung (Journal of Agricultural Engineering), 2025)
Application of fertilizers and mulches can potentially improve crop productivity. However, the effectiveness and sustainability of these inputs depend on how they are managed. The objective of this study is to evaluate the effects of organic and chemical fertilizers, and plastic and bamboo leaf mulches, on the physiological growth and productivity of curly chili (Capsicum annuum L.). Experiment was performed according to a randomized block design with two factors. First factor was fertilizer (P) types consisting of three levels, namely: P0 (no fertilizer), P1 (ecoenzyme organic fertilizer), and P2 (NPK fertilizer). The second factor is the type of mulch (M) consisted of three levels, including M0 (without mulch), M1 (bamboo leaf mulch), and M2 (plastic mulch). Independent parameters included plant height, leaf number, and fruit weight. Results showed that fertilizer type had no significant effect, while plastic mulch significantly improved all parameters. No interaction was observed. These results suggest that plastic mulch effectively enhances chili growth and yield, particularly in the vegetative stage, but its long-term effects warrant further research.   Keywords: Bamboo leaf mulch, Chemical fertilizer, Curly chili, Organic fertilizer, Plastic mulch.